Effect of Routine, Screening Head Ultrasounds on Clinical Interventions for Premature Infants - Heling, Andrew Z.; Laughon, Matthew M.; Price, Wayne A. (American Journal of Perinatology, 2018)
Objective This article assesses whether routine, screening head ultrasound (HUS) studies performed at 7 to 14 postnatal days for premature infants are followed by clinical interventions.Study Design This retrospective cohort study included all inborn infants delivered at < 30 weeks' gestational age (GA) between January 1, 2012 and December 31, 2015 at a single center who had a routine, screening HUS performed between 7 and 14 postnatal days (n = 303). We defined “clinical intervention” as a 7 to 14 postnatal day HUS that was followed by neurosurgical intervention prior to a 36- to 40-week postmenstrual age (PMA) HUS or elective withdrawal of critical care within 30 days of a positive HUS finding.Results Four infants (1.3%) had neurosurgical intervention prior to a 36- to 40-week PMA HUS; all four had a diagnostic HUS performed prior to postnatal day 7 to assess for an intraventricular hemorrhage (IVH) due to clinical instability. No infant had critical care electively withdrawn following a 7 to 14 postnatal day HUS.Conclusion Clinical intervention rarely followed routine, screening HUS studies performed at 7 to 14 postnatal days for inborn infants delivered at < 30 weeks' GA. In no case did clinical intervention related to HUS results occur when a 7 to 14 postnatal day HUS was the initial HUS performed.
Keywords: premature; head ultrasound; screening; intraventricular hemorrhage; intervention